HUBUNGAN KERJASAMA PARIWISATA INDONESIA-KOREA SELATAN TAHUN 2015-2016 - Hidayat, Ikhsan; Harto, Syafri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This is a study about international tourism which gives cooperation analysis among countries through tourism. The international tourism cooperation between Indonesia and South Korea, in this case, makes the cooperation bertween Bali province and Jeju Island government as the focus study in order to facilitate the research. International tourism has become the bridge for international countries to work together and benefit each other.This script uses the conceptual base with the concept of international cooperation where in Indonesia and South Korea become the focus of study. It is also supported by the range or nation-state, global perspective and internation cooperate theory. The concept directs to the qualitative methode and literature study as the resource of the information.The cooperation which was conducted by Indonesia (Bali) and South Korea (Jeju) is in form of promotion improvement with the reciprosity system. Reciprocity is a mutually beneficial cooperation or its other name is win-win solution.Keywords: Cooperation, Tourism, Recyprocity